Motivasi Sebagai Variabel Mediasi Pengaruh Budaya Organisasi Terhadap Kinerja Karyawan - Ni Luh Gede Putu Purnawati; Anak Agung Dwi Widyani; Kadek Dian Putri Anjaya (Universitas Mahendradatta Denpasar, 2022)
This study aims to determine the effect of organizational culture on performance and to determine the role of motivation in mediating it. The research sample consisted of 42 people who were taken using the census method from all employees. The collected data were analyzed using SmartPLS.From the analysis obtained: 1) Organizational culture has a positive and significant influence on motivation. The results of this study indicate that the better the organizational culture can increase motivation. 2) Organizational culture has a positive and significant influence on employee performance. The results of this study mean that the better the implementation of organizational culture will be able to improve employee performance. 3) Motivation has a positive and significant effect on employee performance. The results of this study mean that increased motivation can improve employee performance. 4) Motivation is able to mediate the influence of organizational culture on employee performance. This gives an indication that motivation strengthens the influence of organizational culture on employee performance at PT. Prudential Life Assurance, Patimura Denpasar Branch.